2001
DOI: 10.1177/026765910101600408
|View full text |Cite
|
Sign up to set email alerts
|

Haemolysis due to active venous drainage during cardiopulmonary bypass: comparison of two different techniques

Abstract: To facilitate mini-access for cardiac surgery, two different methods of active venous drainage are used: vacuum assisted drainage and centrifugal pump aspiration on the venous line. The aim of this study was to compare the haemolysis produced using these two techniques. From June to December 1999, 50 consecutive patients were operated on using a ministernotomy. All of these patients had valvular surgery for either valve repair or valve replacement (9 MVRepair, 11 MVR, 29 AVR, 1 AVR + MVR). They were randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 11 publications
(16 reference statements)
3
22
0
1
Order By: Relevance
“…Hp late increase might be associated with an inflammatory reaction as it acts as a moderate acute-phase protein, however, when blood is hemolytic, determination by Hgb binding assays may give unreliable results ( Gruys et al, 2005 ). Our hemolytic parameters measurements are quite consistent with the results obtained by others ( Cirri et al, 2001 ; Mamikonian et al, 2014 ; Vermeulen Windsant et al, 2014 ; Baumbach et al, 2016 ). Sublethal RBC damage results in decreased deformability and surface charge, and increased fragility and aggregability ( Lee et al, 2007 ; Vercaemst, 2008 ) which subsequently lead to the early removal of the RBC from the circulation by the spleen or in the altered rheological proprieties of the blood followed by compromising efficient microcirculation and oxygen delivery to the surrounding tissues ( Watanabe et al, 2007 ; Vercaemst, 2008 ; Ciana et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…Hp late increase might be associated with an inflammatory reaction as it acts as a moderate acute-phase protein, however, when blood is hemolytic, determination by Hgb binding assays may give unreliable results ( Gruys et al, 2005 ). Our hemolytic parameters measurements are quite consistent with the results obtained by others ( Cirri et al, 2001 ; Mamikonian et al, 2014 ; Vermeulen Windsant et al, 2014 ; Baumbach et al, 2016 ). Sublethal RBC damage results in decreased deformability and surface charge, and increased fragility and aggregability ( Lee et al, 2007 ; Vercaemst, 2008 ) which subsequently lead to the early removal of the RBC from the circulation by the spleen or in the altered rheological proprieties of the blood followed by compromising efficient microcirculation and oxygen delivery to the surrounding tissues ( Watanabe et al, 2007 ; Vercaemst, 2008 ; Ciana et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…However, when comparing vacuum drainage with drainage by centrifugal pump, Cirri et al. [ 26 ] showed that the vacuum drainage causes higher degree of hemolysis, according conclusions confirmed by Gregoretti et al [ 27 ] . However, Lau et al [ 28 ] and Shin et al [ 24 ] disagree, showing similar levels of hemolysis.…”
Section: Discussionmentioning
confidence: 96%
“…They found an increase in hemoglobinuria and a decreased platelet count in the VAVD group. Cirri et al 17 concluded that the red cell and platelet damage is reduced when the kinetic assist mode of venous drainage is used. The major disadvantage associated with KAVD is the entrainment of macrobubbles in the venous line, requiring manual clearing of the centrifugal pump.…”
Section: Minimally Invasive Perfusion Techniquesmentioning
confidence: 99%
“…17 The Medtronic Resting Heart System (Medtronic, Minneapolis, Minnesota) alleviates many of these issues providing safe and more efficient perfusion to our MIVS patients. Minimally invasive cardiac surgery itself is very demanding and challenging.…”
Section: Minimally Invasive Perfusion Techniquesmentioning
confidence: 99%